Pemeriksaan Hemoglobin (Hb) Kolaborasi Universitas Pertahanan RI Dengan PMI Kota Bogor - Saragih, Hondor; Pannyiwi, Rahmat; Marunung, Hendra; Harfika, Meiana; Saputra, M. Khalid Fredy; Treasa, Adisty Dwi; Fitriana, Fitriana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hemoglobin is a (metalloprotein) iron-containing protein found in red blood cells giving red blood cells their color. Hemoglobin consists of iron which is an oxygen carrier. Iron-containing proteins enable red blood cells to transport oxygen from the lungs to the rest of the body. Checking hemoglobin levels is one of the routine blood tests needed to diagnose a disease. The purpose of examining hemoglobin levels is to determine hemoglobin levels in the blood, help diagnose anemia, determine body fluid deficits due to increased hemoglobin levels. Methods for examining hemoglobin levels include the Tallquist method, which is an examination based on blood color because Hb plays a role in giving red color to blood erythrocytes, so this examination is carried out by comparing the red color of blood to a standard color where the hemoglobin concentration is known in percent (%) . The results of this Haemoglobin (Hb) examination activity were very smooth and safe according to plan based on the collaboration between the Faculty of Medicine and Health Sciences, Defense University of the Republic of Indonesia and the Indonesian Red Cross of Bogor City in the framework of the XV Anniversary of the Republic of Indonesia Defense University.